Prevalence of Pathogenic Bacteria Isolated from Surgical Site and Wound Infection among Patients Admitted in some selected Hospitals in Sokoto Metropolis, Nigeria - Muhammad, UK; Adamu, TM; Binji, Z; Isa, MA (International Journal of Environment, 2014)
Surgical and open wounds are commonly encountered in clinical practice. This study was aim to determine the prevalence of pathogenic bacteria in surgical and open wound infection among patients admitted in some selected hospitals in Sokoto metropolis. A total of one hundred and fifty one (151) isolates were obtained from two hundred (200) surgical site and wound samples collected from patients in this study. The result showed that Usmanu Danfodiyo Teaching Hospital Sokoto (UDUTH) had the highest number of clinical isolates with 64 gram positive and gram negative bacteria followed by Specialist Hospital Sokoto (S.H.S) with 57 gram positive and gram negative bacteria and then Maryam Abacha Women and Children Hospital (MAWCH) with 30 gram positive and gram negative bacteria. Gram positive cocci 108 (71.5%) were more predominant pathogen isolated in the hospitals than gram negative bacilli 43 (28.5%). Staphylococcus aureus had the highest number of occurrence with 54(35.76%) followed by Coagulate negative Staphylococci with 47(31.1%) while Citrobacter freundii had the lowest number of occurrence with 2(1.32%) isolates. Also, the susceptibility of the isolates to antimicrobial agents were carried out using Amoxacillin, Ampicillin, Erythromycin, Chloramphenicol, Ampiclox, Ciprofloxacin, Gentamycin, Tetracycline, Pefloxacin and Cotrimoxazole. The mean zone of inhibition recorded against Staphlococcus aureus by using Amoxacillin antibiotic is 2.20mm while with Citrobacter freundii is 1.00. DOI: http://dx.doi.org/10.3126/ije.v3i3.11066 International Journal of Environment Vol.3(3) 2014: 89-103